SAT0058 Effects of baricitinib on patients who stop methotrexate monotherapy and switch to baricitinib monotherapy. (15th June 2017) - Fleischmann, R; Takeuchi, T; Schiff, M; Schlichting, D; Xie, L; Issa, M; Stoykov, I; Lisse, JR; Martinez-Osuna, P; Rooney, T; Zerbini, CA
Abstract : Background: Baricitinib (bari) is a reversible oral Janus kinase (JAK) inhibitor with selectivity for JAK1/JAK2 in development for treatment of patients (pts) with active rheumatoid arthritis (RA). In the 52-week (wk) Phase 3 RA-BEGIN study of MTX-naïve pts, there were 3 arms: bari 4 mg once daily (QD), methotrexate (MTX) up to 20 mg weekly (QW), and the combination of bari plus MTX (bari+MTX). Nonresponders were rescued from week 24 onwards by receiving bari+MTX, regardless of original treatment. Bari monotherapy showed superior efficacy compared to MTX monotherapy and similar clinical efficacy to bari+MTX. Objectives: Efficacy and safety were evaluated in pts from RA-BEGIN who switched from MTX or bari+MTX therapy to bari monotherapy upon entering the long-term extension (LTE) study (RA-BEYOND). Methods: In RA-BEGIN, 588 pts were randomised 4:3:4 to MTX, bari monotherapy 4 mg, or bari+MTX. At Wk 52, pts could enter the LTE; all pts received bari 4 mg monotherapy. MTX could be added in the LTE by investigator decision. Seventy-seven percent of pts (451/588) enrolled in the LTE, of whom 423 had not been rescued in RA-BEGIN. This post hoc analysis evaluated clinical efficacy of pts who continued bari monotherapy compared to those in whom MTX was added within the first 24 wks of the LTE. Results: Of these 423 pts, 200 (47%) remained on monotherapy at Wk 24 of the LTE and 223 pts started on MTX before wk 24. Most (193) had initiated MTX within 4 wks of starting the LTE study, evenly balanced from the 3 original arms of RA-BEGIN. Across study arms, pts who had MTX added in the LTE had worse disease control upon entry and during the LTE. Through 24 wks, statistically significant improvement in disease state was observed in the MTX-to-bari group regardless of whether or not MTX was added back. In the bari-to-bari monotherapy group, the addition of MTX led to lowered disease activity, which was statistically significant. No statistically significant changes in disease activity were observed in the pts who were switched from bari+MTX to bari monotherapy regardless of additional MTX therapy (Table 1 ). Exposure-adjusted incidence rates for total treatment-emergent adverse events, including non-serious infections, were lowest in the MTX-to-bari group. Clinically significant or consistent differences in SIE, SAEs, or AEs leading to study drug discontinuation were not seen in any of the arms, whether MTX was added or not. Conclusions: Switching from MTX to bari monotherapy, maintaining bari monotherapy was associated with improvements in depths of disease control during the initial 24 wks post-switch. Disease control did not significantly change after withdrawal of MTX from combination therapy. Pts who entered the LTE with suboptimal disease control after treatment with bari monotherapy may benefit from the addition of MTX. Discontinuation of MTX in pts treated with combination during the index study was associated with maintenance of response. There were no differences in important measures of safety including events that are serious or led to discontinuation. Disclosure of Interest: R. Fleischmann Grant/research support from: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celgene, Genetech, GlaxoSmithKline, Janssen, Eli Lilly and Company, Merck, Pfizer, Regeneron, Roche, Sanofi Aventis, UCB, Consultant for: AbbVie, Akros, Amgen, Bristol-Myers Squibb, Celgene, Genentech, GSK, Janssen, Eli Lilly and Company, Pfizer, Sanofi-Aventis, UCB, T. Takeuchi Consultant for: Pfizer Japan, Astra Zeneca KK, Eli Lilly Japan KK, Novartis Pharma KK, Daiichi Sankyo Co Ltd, Nipponkayaku Ltd, Janssen Pharma KK, Merck Serono Ltd, Takeda Pharma Ltd, Mitsubishi Tanabe Pharma, Astellas Pharm, Abbvie GK, Bristol-Myers KK, Asahi Kasei Medical KK, Speakers bureau: Celtrion, Nipponkayaku Ltd, Pfizer Japan, UCB Japan, Daiichi Sankyo Ltd, Takeda Pharma Ltd, Chugai Pharma Ltd, Abbvie GK, Bristol-Myers KK, Eisai Ltd, Mitsubishi Tanabe Pharma, Janssen Pharma KK, Astellas Pharma, M. Schiff Consultant for: Abbvie, Amgen, Antares, BMS, Eli Lilly and Company, J&J, Novartis, Novo Niordisk, Pfizer, Roche, UCB, Speakers bureau: Abbvie, BMS, D. Schlichting Employee of: Eli Lilly and Company, L. Xie Employee of: Eli Lilly and Company, M. Issa Employee of: Eli Lilly and Company, I. Stoykov Employee of: Eli Lilly and Company, J. Lisse Employee of: Eli Lilly and Company, P. Martinez-Osuna Employee of: Eli Lilly and Company, T. Rooney Employee of: Eli Lilly and Company, C. Zerbini Grant/research support from: Pfizer, Novartis, Eli Lilly and Company, Merck, Sanofi, Amgen, Celtrion, Consultant for: Merck, Pfizer, Sanofi, Eli Lilly and Company